2018
DOI: 10.1111/bjd.16089
|View full text |Cite
|
Sign up to set email alerts
|

Supervised exercise training as an adjunct therapy for venous leg ulcers: a randomized controlled feasibility trial

Abstract: SummaryBackgroundVenous leg ulcers (VLUs) are typically painful and heal slowly. Compression therapy offers high healing rates; however, improvements are not usually sustained. Exercise is a low‐cost, low‐risk and effective strategy for improving physical and mental health. Little is known about the feasibility and efficacy of supervised exercise training used in combination with compression therapy patients with VLUs.ObjectivesTo assess the feasibility of a 12‐week supervised exercise programme as an adjunct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(119 citation statements)
references
References 28 publications
5
111
0
1
Order By: Relevance
“…However, 100% of the participants were adherent to our 6-week exercise program more than 85% of the time in terms of duration, whereas 33% of the participants adhered more than 85% in terms of frequency of exercises. This finding is lower than findings of a 12-week home-based program in which 59% of individuals adhered to exercise more than 75% of the time [ 8 ]. Current evidence of mHealth interventions to promote physical activity demonstrate positive short-term effects (increased daily step counts and minutes spent on physical activity); however, evidence for long-term effects is lacking [ 28 ].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, 100% of the participants were adherent to our 6-week exercise program more than 85% of the time in terms of duration, whereas 33% of the participants adhered more than 85% in terms of frequency of exercises. This finding is lower than findings of a 12-week home-based program in which 59% of individuals adhered to exercise more than 75% of the time [ 8 ]. Current evidence of mHealth interventions to promote physical activity demonstrate positive short-term effects (increased daily step counts and minutes spent on physical activity); however, evidence for long-term effects is lacking [ 28 ].…”
Section: Discussionmentioning
confidence: 59%
“…Exercise is recommended for patients with VLUs to enhance calf muscle pump function, which, in turn, improves lower extremity function and may aid in wound healing. Supervised and unsupervised programs that incorporate resistance, flexibility, and moderate-intensity aerobics can be safely performed by individuals with VLUs [ 8 ]. Other benefits of exercise include improved microvascular circulation of the lower limb [ 26 , 27 ] and improved wound healing [ 9 , 10 ]; however, a recent review of six randomized controlled trials to examine the effects of exercise on healing showed high-quality evidence is lacking to support healing [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These should be sufficiently effective to either reverse or slow-down the progression of these diseases and conditions, not only enhancing treatment, but also improving patients' quality of life. Exercise has been earmarked as one of the main lifestyle components that could be introduced in therapeutic interventions, as it is usually easy to implement by facilitators and be followed by clinical populations (i.e., Klonizakis et al, 2018 ; Mitropoulos et al, 2020 ), offering also societal and quality of life benefits (Kesterton et al, 2019 ).…”
mentioning
confidence: 99%
“…The current issue of the BJD contains an interesting article from Klonizakis et al ., which reports that the proportion of ulcers healed at 12 months was higher in patients receiving conventional compression therapy and adjunctive supervised exercise training than in those receiving compression alone (83% vs. 60%). This randomized controlled feasibility trial contradicts a Cochrane review from 2016, which found inadequate evidence to make a recommendation for exercise in nonulcerated chronic venous insufficiency, and a study of home exercise programmes that failed to find any significant association with VLU healing .…”
mentioning
confidence: 99%